Oxygen vacancy defect type ferroferric oxide Fenton-like material and preparation method and application thereof

By using oxygen vacancies defective iron tetraoxide Fenton materials, the problems of low metal circulation efficiency and high hydrogen peroxide consumption in the prior art are solved, and efficient catalytic degradation effect is achieved, which is suitable for treating antibiotic-contaminated water bodies.

CN116282473BActive Publication Date: 2025-04-18HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310256684.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-04-18
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

In the existing heterogeneous Fenton reaction dominated by iron tetraoxide, divalent iron is depleted by hydrogen peroxide and the reduction rate of trivalent iron is too slow, resulting in low metal circulation efficiency, large hydrogen peroxide consumption, and low degradation efficiency.

Method used

The oxygen vacancy defective ferrotrioxide Fenton material is used. This material is made of nanosheets to form a flower-like structure, and has abundant oxygen vacancy defects. The morphology and oxygen vacancy defect content are regulated through sodium borohydride to improve catalytic efficiency.

Benefits of technology

The metal circulation efficiency of iron tetroxide surface is improved, hydrogen peroxide consumption is reduced, hydroxyl radical generation ability is enhanced, and the degradation efficiency of antibiotic-contaminated water bodies is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282473B_ABST
    Figure CN116282473B_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen vacancy defect type ferroferric oxide Fenton-like material and its preparation method and application. The material is composed of ferroferric oxide, and ferroferric oxide presents a flower-like structure formed by nanosheet accumulation, and there are abundant oxygen vacancy defects on ferroferric oxide. The preparation method includes mixing and stirring a ferrous sulfate solution with a ferric chloride solution, adding ammonia water dropwise to the obtained mixed solution and stirring, and adding a sodium borohydride solution dropwise to the obtained ferroferric oxide precursor, stirring, cleaning, and drying to obtain a product. The Fenton-like material of the present invention has the advantages of high catalytic efficiency, good stability, high recycling rate, low cost and environmental friendliness, and can be widely used in catalytic removal of antibiotics in polluted water bodies. The preparation method has easy-to-obtain raw materials, simple operation, green and environmentally friendly, suitable for large-scale preparation, and meets the needs of actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced oxidation treatment in environmental pollution, and specifically relates to an oxygen vacancy defect type ferroferric oxide Fenton-type material and a preparation method thereof. Background Art

[0002] In recent years, antibiotics have been continuously detected in water bodies, which has become a major environmental pollution problem. Antibiotics that enter the body are difficult to be completely absorbed, and most of them are excreted in their original form. Antibiotics discharged into water bodies are difficult to remove through the self-purification of the water body, which will promote the formation or enhancement of drug resistance in aquatic organisms and even induce the production of resistance genes. Aquatic organisms with drug resistance enter the human body through the food chain, which seriously threatens human safety and health. Therefore, exploring new technologies for treating antibiotic pollution in water bodies has become an important issue in today's society.

[0003] Heterogeneous Fenton-like technology is a rapidly developing method for remediating water bodies polluted by organic pollutants such as antibiotics in recent years. This method activates hydrogen peroxide through Fenton-like catalysts to produce highly active hydroxyl radicals with extremely strong oxidizing ability, which mix and react with organic pollutants such as antibiotics, thereby degrading the pollutants into low-toxic or non-toxic chemical forms. In this process, heterogeneous Fenton-like catalysts play a core and leading role in catalytic efficiency. Therefore, finding a suitable catalyst has become the key to applying heterogeneous Fenton-like technology to treat antibiotic-contaminated water bodies.

[0004] Therefore, ferroferric oxide, which is abundant in nature and environmentally friendly, has attracted great attention. Ferroferric oxide is a magnetic iron oxide with an inverse spinel structure. It is composed of lattice oxygen ions densely packed in a face-centered cubic pattern, and divalent iron ions and trivalent iron ions are distributed in the gaps of the densely packed oxygen ions. The presence of divalent iron ions in its structure makes it easier to react with hydrogen peroxide to generate highly active hydroxyl radicals; at the same time, ferroferric oxide also has the advantages of simple synthesis method, wide source of raw materials, and high chemical stability. In the traditional heterogeneous Fenton-like reaction dominated by ferroferric oxide, hydrogen peroxide forms a surface complex with the divalent iron on the surface of ferroferric oxide, and electron transfer occurs between hydrogen peroxide and divalent iron in the complex, thereby generating trivalent iron and highly active hydroxyl radicals. However, the oxidizing effect of hydrogen peroxide quickly depletes the divalent iron, but the rate at which trivalent iron is reduced to divalent iron by hydrogen peroxide is too slow (k = 0.001-0.02M -1 S -1), which limits the regeneration of divalent iron; in addition, during the process of reducing trivalent iron to divalent iron by hydrogen peroxide, hydrogen peroxide is decomposed into peroxide radicals with relatively low oxidation ability, which reduces the utilization rate of hydrogen peroxide and ultimately reduces the generation of hydroxyl radicals in the system, which is not conducive to the efficient catalytic degradation of organic pollutants under the condition of a small amount of hydrogen peroxide. Therefore, how to effectively improve the metal circulation efficiency on the surface of ferroferric oxide and reduce the consumption of hydrogen peroxide is a thorny problem faced in existing scientific research. How to develop Fenton-like materials that can effectively overcome the above problems is of great significance to expanding the application scope of Fenton technology. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an oxygen vacancy defect type ferroferric oxide Fenton material with high catalytic efficiency, which can effectively improve the metal circulation efficiency on the surface of ferroferric oxide, reduce hydrogen peroxide consumption, have good stability, high recycling rate, low cost and be environmentally friendly. Correspondingly, a preparation method and application of an oxygen vacancy defect type ferroferric oxide Fenton material with mild reaction conditions, simple operation process, green and environmental protection and can be used for large-scale production are also provided.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions.

[0007] An oxygen vacancy defect type ferroferric oxide Fenton material, wherein the oxygen vacancy defect type ferroferric oxide Fenton material is composed of ferroferric oxide, the ferroferric oxide presents a flower-like structure formed by stacking nanosheets, oxygen vacancy defects exist on the ferroferric oxide, and the oxygen vacancy defects are anion defects.

[0008] As a general technical concept, the present invention also provides a method for preparing the above-mentioned oxygen vacancy defect type ferroferric oxide Fenton-like material, comprising the following steps:

[0009] S1, mixing ferrous sulfate solution and ferric chloride solution, stirring to obtain a mixed solution of ferrous sulfate and ferric chloride;

[0010] S2, adding ammonia water dropwise to the mixture of ferrous sulfate and ferric chloride, stirring, to obtain a ferrosoferric oxide precursor;

[0011] S3. Adding sodium borohydride solution dropwise to the ferroferric oxide precursor, wherein the volume ratio of the ammonia water to the sodium borohydride solution is 1:0.83-1, stirring, washing and drying to obtain an oxygen vacancy defect ferroferric oxide Fenton-type material.

[0012] In the above-mentioned method for preparing the oxygen vacancy defect type ferroferric oxide Fenton-type material, preferably, in step S1, the molar ratio of the divalent iron in the ferrous sulfate solution to the trivalent iron in the ferric chloride solution is 1:2.

[0013] The preparation method of the above-mentioned oxygen vacancy defect type ferroferric oxide Fenton material, preferably, in step S1, the ferrous sulfate solution is prepared by dissolving ferrous sulfate heptahydrate in anaerobic water, and the concentration of the ferrous sulfate solution is 1 mol / L, and the ferric chloride solution is prepared by dissolving ferric chloride hexahydrate in anaerobic water, and the concentration of the ferric chloride solution is 2 mol / L; the stirring is carried out at room temperature.

[0014] In the above-mentioned method for preparing oxygen vacancy defect type ferroferric oxide Fenton-type material, preferably, the volume ratio of the ferric chloride solution in step S1 to the ammonia water in step S2 is 1:0.6-1, and the mass fraction of the ammonia water is 25%-28%.

[0015] In the above-mentioned method for preparing oxygen vacancy defect-type ferroferric oxide Fenton-type material, preferably, in step S3, the sodium borohydride solution is prepared by dissolving sodium borohydride in oxygen-free water, and the concentration of the sodium borohydride solution is 1 mol / L to 4 mol / L.

[0016] In the above-mentioned method for preparing oxygen vacancy defect-type ferroferric oxide Fenton-type material, preferably, in step S2, the stirring is carried out in a water bath at 75° C. to 85° C., and the stirring time is 3 min to 6 min.

[0017] In the above-mentioned method for preparing oxygen vacancy defect-type ferroferric oxide Fenton-type material, preferably, in step S3, the stirring is carried out in a water bath at 75° C. to 85° C., and the stirring time is 110 min to 120 min.

[0018] In the above-mentioned method for preparing oxygen vacancy defect-type ferroferric oxide Fenton material, preferably, in step S3, the cleaning is performed by alternating water and ethanol for 3 to 5 times; the drying atmosphere is vacuum, the drying temperature is 60°C to 70°C, and the drying time is 12h to 16h.

[0019] As a general technical concept, the present invention also provides an application of the above-mentioned oxygen vacancy defect type ferroferric oxide Fenton material or the oxygen vacancy defect type ferroferric oxide Fenton material prepared by the above-mentioned preparation method in treating antibiotic-contaminated water.

[0020] Compared with the prior art, the advantages of the present invention are:

[0021] 1. The present invention provides an oxygen vacancy defect-type ferroferric oxide Fenton material, which has a flower-like structure and contains abundant oxygen vacancy defects. The invention uses ferroferric oxide as a main material, has the advantages of being environmentally friendly, low cost, high stability, strong magnetism, etc., and has the ability to decompose hydrogen peroxide. On this basis, sodium borohydride is used to simultaneously regulate the morphology and the content of oxygen vacancy defects, so that the utilization efficiency of ferroferric oxide for hydrogen peroxide can be effectively improved, and efficient activation of hydrogen peroxide can be achieved. Specifically, on the one hand, the flower-like structure enables ferroferric oxide to expose more active sites to contact with hydrogen peroxide, thereby promoting the decomposition of hydrogen peroxide into hydroxyl radicals; on the other hand, the oxygen vacancy defects can regulate the electronic structure of ferroferric oxide, which is beneficial to the existence of divalent iron in the ferroferric oxide structure; in addition, due to the unsaturated coordination of atoms around the oxygen vacancy defects, a large number of dangling bonds can be provided for the adsorption of substrate molecules, and the localized electrons around the oxygen vacancy defects are relatively large, so that the ferroferric oxide can be used as an electron-rich active center to promote metal cycle reactions and activation of substrate molecules, and the technical problems of a single active center on the surface of ferroferric oxide and a low utilization rate of hydrogen peroxide are effectively solved. It can be seen that the oxygen vacancy defect-type ferroferric oxide Fenton-like material of the present invention is a new type of heterogeneous Fenton-like catalytic material with excellent catalytic performance, which can effectively improve the metal circulation efficiency on the surface of ferroferric oxide and reduce the consumption of hydrogen peroxide.

[0022] 2. In the oxygen vacancy defect type ferroferric oxide Fenton material of the present invention, ferroferric oxide is widely present in nature, and iron is a trace element necessary for the human body. Even if a trace amount of leaching occurs, it will not cause toxic effects on animals and plants, and is more in line with the modern scientific and technological standards of green, environmentally friendly, high quality and low price. Therefore, the oxygen vacancy defect type ferroferric oxide Fenton material is a new type of green, environmentally friendly and economical Fenton material.

[0023] 3. The present invention also provides a method for preparing an oxygen vacancy defect type ferroferric oxide Fenton catalytic material, wherein a ferrous sulfate solution, a ferric chloride solution, and an ammonia solution are used as raw materials to prepare a ferroferric oxide precursor, and then the morphology and oxygen vacancy defect content are simultaneously regulated by sodium borohydride to obtain an oxygen vacancy defect type ferroferric oxide Fenton material. After sodium borohydride is added to the ferroferric oxide precursor, it can change the anisotropic growth rate of the ferroferric oxide crystal by adsorbing on the surface of the precursor or embedding in the precursor lattice, thereby affecting the nucleation process and growth process of the ferroferric oxide crystal, and finally realizing the regulation of the microscopic morphology of ferroferric oxide. At the same time, the interaction between the strongly reducing hydrogen in sodium borohydride and the ferroferric oxide precursor can induce the generation of more oxygen vacancy defects to maintain the non-stoichiometric overall charge balance in the lattice. The preparation method of the present invention is a one-step control method, which has lower operating cost and is simpler and easier to operate than the conventional two-step control method, and does not require high-temperature calcination under nitrogen / hydrogen conditions or reaction under high temperature and high pressure, so that oxygen vacancy defects can be more abundant. It can be seen that the preparation method of the oxygen vacancy defect type ferroferric oxide Fenton material of the present invention has the advantages of simple process, convenient operation, wide source of raw materials, low cost, mild reaction conditions, green and environmental protection, etc., is suitable for large-scale preparation, is conducive to industrial utilization, and is more in line with the current concept of sustainable development.

[0024] 4. In the preparation method of the oxygen vacancy defect type ferroferric oxide Fenton material of the present invention, by optimizing the volume ratio of ammonia water and sodium borohydride solution to 1: 0.83-1, the generation of oxygen vacancy defects in ferroferric oxide can be more accurately regulated, thereby obtaining better catalytic performance. When the ratio of ammonia water and sodium borohydride is too high, the content of oxygen vacancy defects on the surface of ferroferric oxide is too low, which is not conducive to the improvement of catalytic performance; when the ratio of ammonia water and sodium borohydride is too low, excessive sodium borohydride easily reduces iron ions to nano zero-valent iron, which is not conducive to the generation of ferroferric oxide and also increases operating costs.

[0025] 5. The remediation efficiency of the oxygen vacancy defect type ferroferric oxide Fenton material of the present invention for antibiotic-contaminated water under dynamic conditions is also another criterion for measuring its practical application. In the present invention, the oxygen vacancy defect type ferroferric oxide Fenton material has excellent continuous removal ability. The oxygen vacancy defect type ferroferric oxide Fenton material is mixed with quartz sand and placed in a fixed bed Fenton reactor to effectively treat water containing oxygen tetracycline, and the catalytic effect within 120 hours is always maintained at a high level. It can be seen that the oxygen vacancy defect type ferroferric oxide Fenton material of the present invention has the advantages of excellent stability and strong practicality, and is a new type of Fenton material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is a scanning electron microscope image of the oxygen vacancy defect-type ferroferric oxide Fenton-like material (A2) prepared in Example 1 of the present invention.

[0027] Figure 2 This is the energy spectrum of the oxygen vacancy defect-type ferroferric oxide Fenton material (A2) prepared in Example 1 of the present invention.

[0028] Figure 3 X-ray diffraction patterns of the oxygen vacancy defect-type ferroferric oxide Fenton-like materials (A2, A3) prepared in Examples 1 and 2 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1.

[0029] Figure 4 These are electromagnetic resonance spectra of the oxygen vacancy defect-type ferroferric oxide Fenton-like materials (A2, A3) prepared in Examples 1 and 2 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1.

[0030] Figure 5 It is a differential charge density diagram of the oxygen vacancy defect-type ferroferric oxide Fenton-like material (A2) prepared in Example 1 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1.

[0031] Figure 6 This is a diagram showing the degradation effects of oxygen vacancy defect-type ferroferric oxide Fenton materials (A2, A3) in Example 3 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1 on oxytetracycline. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the scope of protection of the present invention is not limited thereby. The materials and instruments used in the following examples are all commercially available. In the following examples, unless otherwise specified, the data obtained are the average values ​​of more than three repeated experiments.

[0033] Example 1

[0034] An oxygen vacancy defect type ferroferric oxide Fenton material of the present invention, such as Figure 1 As shown, the material is composed of ferroferric oxide, and the morphology of ferroferric oxide is a flower-like structure. There are abundant oxygen vacancy defects on the ferroferric oxide, and the oxygen vacancy defects are anion defects.

[0035] A method for preparing an oxygen vacancy defect-type ferroferric oxide Fenton-type material of this embodiment comprises the following steps:

[0036] S1. Dissolve 27.801 g of ferrous sulfate heptahydrate in 100 mL of oxygen-free water to obtain a 1 mol / L ferrous sulfate solution. Dissolve 54.058 g of ferric chloride hexahydrate in 100 mL of oxygen-free water to obtain a 2 mol / L ferric chloride solution. Mix 20 mL of ferrous sulfate solution and 20 mL of ferric chloride solution, and stir to obtain a mixed solution of ferrous sulfate and ferric chloride.

[0037] S2. Add 12 mL of aqueous ammonia dropwise into the mixture of ferrous sulfate and ferric chloride, wherein the mass fraction of aqueous ammonia is 25%-28%, and stir magnetically for 5 minutes in a water bath at 80° C. to obtain a ferrosoferric oxide precursor.

[0038] S3, 7.566g sodium borohydride was dissolved in 100mL oxygen-free water to obtain a 2mol / L sodium borohydride solution. 12mL of sodium borohydride solution was added dropwise to the ferroferric oxide precursor, and magnetic stirring was performed for 2h in a water bath at 80°C. The resulting mixture was washed alternately with ultrapure water and anhydrous ethanol for 3 times, and the solid obtained after washing was placed in a vacuum drying oven and dried at 60°C for 12h to obtain an oxygen vacancy defect type ferroferric oxide Fenton material (A2).

[0039] Example 2

[0040] An oxygen vacancy defect type ferroferric oxide Fenton material of the present invention is basically the same as the oxygen vacancy defect type ferroferric oxide Fenton material of Example 1, except that the volume ratio of ammonia water to sodium borohydride solution in the oxygen vacancy defect type ferroferric oxide Fenton material of Example 2 is 1:0.83.

[0041] A method for preparing an oxygen vacancy defect type ferroferric oxide Fenton material of this embodiment is basically the same as the method for preparing an oxygen vacancy defect type ferroferric oxide Fenton material in Example 1, with the only difference being that the volume of the sodium borohydride solution in step S3 of the preparation method of Example 2 is 10 mL.

[0042] The oxygen vacancy defect-type ferroferric oxide Fenton-type material prepared in Example 2 is numbered A3.

[0043] Comparative Example 1

[0044] A method for preparing a ferrosoferric oxide monomer material comprises the following steps:

[0045] (1) Dissolve 27.801 g of ferrous sulfate heptahydrate in 100 mL of oxygen-free water to obtain a ferrous sulfate solution. Dissolve 54.058 g of ferric chloride hexahydrate in 100 mL of oxygen-free water to obtain a ferric chloride solution. Mix 20 mL of the above ferrous sulfate solution and ferric chloride solution and stir. Then add 12 mL of ammonia water dropwise, and stir magnetically for 5 minutes in a water bath at 80°C to obtain a ferrosoferric oxide precursor.

[0046] (2) 12 mL of oxygen-free water was added dropwise to the ferroferric oxide precursor obtained in step (1), and the mixture was magnetically stirred in a water bath at 80° C. for 2 h. The resulting mixture was washed three times with ultrapure water and anhydrous ethanol alternately, and the solid obtained after washing was placed in a vacuum drying oven and dried at 60° C. for 12 h to obtain ferroferric oxide monomer material (A1).

[0047] Figure 1 FIG. 1 is a scanning electron microscope image of oxygen vacancy defect-type ferroferric oxide (A2) prepared in Example 1 of the present invention. Figure 1 It can be seen that the oxygen vacancy defect-type ferroferric oxide mainly presents a flower-like structure formed by the accumulation of nanosheets.

[0048] Figure 2 The energy spectrum of oxygen vacancy defect type ferroferric oxide (A2) prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that the oxygen vacancy defect-type ferroferric oxide mainly contains Fe and O elements. Figure 3 The X-ray diffraction patterns of the oxygen vacancy defect type ferroferric oxide (A2, A3) prepared in Examples 1 and 2 of the present invention and the ferroferric oxide monomer material prepared in Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the oxygen vacancy defect-type ferroferric oxide (A2, A3) materials only show the characteristic peak of Fe3O4, proving the successful synthesis of ferroferric oxide.

[0049] Figure 4 The electromagnetic resonance spectra of the oxygen vacancy defect type ferroferric oxide Fenton materials (A2, A3) prepared in Examples 1 and 2 of the present invention and the ferroferric oxide monomer material prepared in Comparative Example 1 are shown in FIG. Figure 4 It can be seen that both the oxygen vacancy defect-type iron oxide Fenton materials (A2, A3) and the iron oxide monomer materials have a signal peak with a g value of 2.003, and the signal peak intensity of the oxygen vacancy defect-type iron oxide Fenton materials is higher, which further illustrates that the oxygen vacancy defect-type iron oxide Fenton materials have a higher oxygen vacancy defect content.

[0050] Figure 5 The differential charge density diagram is a graph of the oxygen vacancy defect type ferroferric oxide Fenton-like material (A2) prepared in Example 1 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1. Figure 5 It can be seen that compared with A1, after the introduction of oxygen vacancy defects in A2, the electron density near iron increases, further proving that oxygen vacancy defects can improve the metal cycle efficiency on the surface of ferroferric oxide.

[0051] From the above, it can be seen that the present invention has successfully prepared an oxygen vacancy defect type ferroferric oxide Fenton material. The obtained oxygen vacancy defect type ferroferric oxide Fenton material presents a flower-like structure formed by stacking nanosheets, which can expose more active sites for contact reaction with hydrogen peroxide. At the same time, the oxygen vacancy defect content is significantly increased compared with ferroferric oxide, which is more conducive to the presence of divalent iron in the ferroferric oxide structure, thereby facilitating the decomposition of hydrogen peroxide into highly active hydroxyl radicals.

[0052] Example 3

[0053] The degradation efficiency of oxytetracycline in water by the oxygen vacancy defect-type ferroferric oxide Fenton-like materials (A2, A3) prepared in Examples 1 and 2 of the present invention and the ferroferric oxide monomer material (A1) prepared in Comparative Example 1 was investigated.

[0054] Weigh 5 mg of the ferroferric oxide monomer material (A1) in Comparative Example 1 and the oxygen vacancy defect-type ferroferric oxide Fenton-like materials (A2 and A3) prepared in Examples 1 and 2 of the present invention, respectively, and add them to 100 mL and 10 mg / L of oxytetracycline solution, respectively, the pH value of the solution is 4.7, and stir for 30 minutes in the dark to allow oxytetracycline to reach adsorption-desorption equilibrium on the catalyst surface; then add 200 μL of hydrogen peroxide solution, the concentration of the hydrogen peroxide solution is 1 mol / L, and continue stirring for 1 hour to carry out a Fenton-like reaction, thereby completing the degradation of oxytetracycline in the water.

[0055] Blank group: 100 mL of 10 mg / L oxytetracycline solution (pH 5.6) was taken without adding any catalyst material, and 200 μL of 1 mol / L hydrogen peroxide solution was added, and then treated under the same conditions as a control.

[0056] During the Fenton-like reaction, a sample was taken every 10 minutes, and the sample was filtered through a 0.22 μm microporous membrane filter. The concentration change of oxytetracycline was analyzed by high performance liquid chromatography to obtain the degradation efficiency of oxytetracycline by different materials. The results are as follows: Figure 6 shown.

[0057] Figure 6 The figure shows the degradation effect of ferroferric oxide monomer material (A1) and oxygen vacancy defect ferroferric oxide Fenton-like materials (A2, A3) on oxytetracycline. Figure 6It can be seen that under low catalyst dosage and low hydrogen peroxide dosage, the oxygen vacancy defect type ferroferric oxide Fenton material (A2) of the present invention has the best degradation effect on oxytetracycline, and the degradation efficiency of oxytetracycline in 90 minutes reaches 91.6%. When the dosage of sodium borohydride is reduced to 10mL, the degradation efficiency of oxytetracycline in 90 minutes of the oxygen vacancy defect type ferroferric oxide material (A3) drops to 72.3%; this is because the oxygen vacancy defect content generated by the reduction of the ferroferric oxide precursor by a small amount of sodium borohydride is relatively small, which reduces the number of active sites, thereby reducing the activation of hydrogen peroxide and reducing the catalytic effect of the material. In the present invention, when sodium borohydride is not added, the degradation efficiency of oxytetracycline in 90 minutes of the ferroferric oxide monomer material (A1) is only 35.4%. It can be seen that when the volume ratio of ammonia water to sodium borohydride is 1:1, the degradation efficiency of pollutants by the oxygen vacancy defect type ferroferric oxide Fenton material (A2) is the best.

[0058] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing an oxygen vacancy defect type ferroferric oxide Fenton-like material, characterized in that: The following steps are involved: S1, mixing ferrous sulfate solution and ferric chloride solution, stirring to obtain a mixed solution of ferrous sulfate and ferric chloride; S2, adding ammonia water dropwise to the mixture of ferrous sulfate and ferric chloride, stirring, to obtain a ferrosoferric oxide precursor; S3, adding sodium borohydride solution dropwise to the ferroferric oxide precursor, wherein the volume ratio of the ammonia water to the sodium borohydride solution is 1:1, stirring, washing, and drying to obtain an oxygen vacancy defect-type ferroferric oxide Fenton-like material; The oxygen vacancy defect type ferroferric oxide Fenton material is composed of ferroferric oxide, and the ferroferric oxide presents a flower-like structure formed by stacking nanosheets. There are oxygen vacancy defects on the ferroferric oxide, and the oxygen vacancy defects are anion defects.

2. The method for preparing the oxygen vacancy defect type ferroferric oxide Fenton-like material according to claim 1, characterized in that: In step S1, the molar ratio of the divalent iron in the ferrous sulfate solution to the trivalent iron in the ferric chloride solution is 1:

2.

3. The method for preparing the oxygen vacancy defect type ferroferric oxide Fenton-like material according to claim 2, characterized in that: In step S1, the ferrous sulfate solution is prepared by dissolving ferrous sulfate heptahydrate in oxygen-free water, and the concentration of the ferrous sulfate solution is 1 mol / L; the ferric chloride solution is prepared by dissolving ferric chloride hexahydrate in oxygen-free water, and the concentration of the ferric chloride solution is 2 mol / L; and the stirring is performed at room temperature.

4. The method for preparing the oxygen vacancy defect type ferroferric oxide Fenton-like material according to claim 2, characterized in that: The volume ratio of the ferric chloride solution in step S1 to the ammonia water in step S2 is 1:0.6-1, and the mass fraction of the ammonia water is 25%-28%.

5. The method for preparing an oxygen vacancy defect type ferroferric oxide Fenton-type material according to any one of claims 1 to 4, characterized in that: In step S3, the sodium borohydride solution is prepared by dissolving sodium borohydride in oxygen-free water, and the concentration of the sodium borohydride solution is 1 mol / L to 4 mol / L.

6. The method for preparing an oxygen vacancy defect type ferroferric oxide Fenton-type material according to any one of claims 1 to 4, characterized in that: In step S2, the stirring is performed in a water bath at 75°C to 85°C, and the stirring time is 3 min to 6 min.

7. The method for preparing an oxygen vacancy defect-type ferroferric oxide Fenton-type material according to any one of claims 1 to 4, characterized in that: In step S3, the stirring is performed in a water bath at 75° C. to 85° C., and the stirring time is 110 min to 120 min.

8. The method for preparing the oxygen vacancy defect type ferroferric oxide Fenton-type material according to any one of claims 1 to 4, characterized in that: In step S3, the cleaning is performed by alternately washing with water and ethanol for 3 to 5 times; the drying atmosphere is vacuum, the drying temperature is 60° C. to 70° C., and the drying time is 12 h to 16 h.

9. Use of an oxygen vacancy defect type ferroferric oxide Fenton material prepared by the preparation method according to any one of claims 1 to 8 in treating antibiotic-contaminated water.